Combating Metabolic Syndrome through Non-Pharmacological Strategies: A Literature Review: Combating Metabolic Syndrome - Aziz, Zubia; Shareef, Huma; Afridi, Eesha; Kashif, Musab; Hussain, Makashfa; Waseem, Maria; Shahid, Talha; Khan, Muhammad Arsalan; Muntaha, Sidra Tul; Hameed Silro, Hallar (Pakistan Journal of Health Sciences, 2023)
Metabolic syndrome (MetS) represents a constellation of interlinked metabolic abnormalities, encompassing hypertension (HTN), insulin resistance diabetes, obesity, and atherogenic dyslipidemia. It is observed that people suffering from these symptoms of metabolic syndrome are twice as likely to develop cardiovascular diseases (CVDS) and five times more likely to develop Type 2 Diabetes Mellitus (T2DM) during their lifetime. The alarming increase in the incidence of MetS, in population worldwide, has made it an epidemic. In today’s world people are more susceptible to MetS due to their sedentary lifestyle, bad eating habits, and various forms of stress. Knowing the socioeconomic burden of disease of MetS on global health throughout the years has brought attention towards its management and therapeutic approach and rightly so, this has also created the need for new, innovative, and non-traditional methods of managing MetS, as the current available treatments of MetS have limited efficacy. In this review, we highlight the prevalence, definition and also summarize the latest non-traditional therapies of MetS worldwide.